Prevalência e fenotipagem eritrocitária em doadores de sangue no Hemocentro Regional de Santa Maria - Bortolotto, Adriana Najai Stein (2011)
The knowledge of the variability of antigens of blood groups is essential in the transfusional practice, mainly to avoid grave alloimmunizations. This study had as objective to evaluate the prevalence of the phenotypes from the blood donors from Santa Maria´s Blood Center. These donors were evaluated for the mainly antigens of ABO, Rh and Kell systems. About the phenotyped samples with Rh system, 1274 samples (54.18%) were phenotyped as positives Rh and 1077 samples (45.82%) phenotyped as negative Rh. From the phenotyped donors as negatives Rh, 103 samples (9.5%) were positives for the ―C‖ or ―E‖ antigen. Relating the percentage of the Kell system positive in donors with negative Rh, was gotten 8.3%. We concluded that the negative Rh donor must be analyzed for other antigens of Rh system and for the Kell antigen, exactly being less immunogenics, these antigens are able to cause Grave Hemolytic Disease and Alloimmunizations. The D antigen Phenotypic expression may vary due to changes qualitative/quantitative: weak D, partial D. This study analyzed a sample of donors by genotyping to identify the most common D variants in this region was found (44%) weak D, (3%) and partial D. Strengthens thus the importance of established protocols for use of rare blood and ensure the proper use of blood products, as well as the safety of blood transfusion.